Lippia mantiqueirae (Verbenaceae), a new species from Minas Gerais, Brazil - Cardoso, Pedro Henrique; Menini Neto, Luiz; Salimena, Fátima Regina Gonçalves (Phytotaxa, 2019)
Lippia mantiqueirae, a new Verbenaceae species endemic to the campos de altitude of Serra da Mantiqueira in Minas Gerais state, Brazil, is described and illustrated. It is morphologically most similar to Lippia triplinervis, but can be distinguished by presenting petiolate leaves, ovate, oval-elliptic or obovate blades with cuneate base, 3-6 pairs of suprabasal secondary veins and unequal bracts, the external oblong-elliptical and the internal lanceolate. Additionally, distribution map, habitat information, field photographs and conservation assessment are provided for the new species.